The sequence stratigraphy of the Lower Jurassic of Western Europe - Parkinson, DN (1994)
﻿ The Lower Jurassic stratigraphy of seven contrasting areas in western Europe is compared in order to seek evidence for a pan-Western European stratigraphic forcing mechanism. Sequencestratigraphic models are discussed and emphasis is placed upon the differing response of sedimentary systems in "accommodation space-dominated" and "supply-dominated" settings. Spectral gamma-ray data from clastic successions in the Wessex and Cleveland basins (England) are used to elucidate vertical trends. A proximal-distal model for control of Th/K ratios is advanced. Stage-frequency regressive-transgressive cycles in the two areas are shown to be closely correlative. Sedimentolgical logs and spectral gamma-ray data are presented for the carbonate ramp into turbidite sequence of Peniche (Portugal) and for a new exposure of the Pliensbachian-Toarcian in southern Germany. Systematic variation in clay mineralogy across Europe is suggested. Cycles in the Lower Jurassic of the North Viking Graben (Norwegian North Sea) are examined using wireline log correlation and the stratigraphic evolution of the Tethyan Rift in the Western and Southern Alps is reviewed. X-ray diffraction studies of the Pliensbachian-Toarcian interval in the Southern Alps are presented in order to elucidate sediment supply to the pelagic realm. The cycles observed in the English sections appear to be manifest widely across western Europe in a variety of tectonic and sedimentary settings. Sharp basinward facies shifts (candidate sequence boundaries) do not appear to be synchronous between basins. 87SR/86SR analysis of belemnites from the Portuguese and German sections confirms the regional applicability of the results of Jones (1992) and the utility of this technique in long range correlation. Carbon and oxygen analysis of the same material supplements the data of other workers and a direct relationship is suggested between relative sea level and organic carbon burial in the Early Jurassic.